Images of Children in Igbo Aetiological Tales - Chukwuneke, Ogechukwu F. U.; Ezebube , Chinedu C. (Khwopa Journal, 2025)
Humans seek to mediate meaning and assign order to their rather chaotic world. In the pursuit of meaning and to account for phenomena, they coin tales for things and situations they cannot otherwise explain. Cultures all over the world have their aetiological tales, stemming from their ideology, which accounts for why things happen or are the way they are. Through their aetiological tales, the beliefs, culture and tradition of the Igbo regarding the creator and the created are exposed. The child is one component of society that is considered important. Nonetheless, it is conceptualised differently in each culture. The study, therefore, seeks to determine how the child is conceived of in Igbo ideology through Igbo aetiological tales. Eleven tales are purposively selected from Eke na egwurugwu, a book of aetiological tales. The research methodology adopted is qualitative; the tales are analysed using the precepts of paradigmatic structuralism to decipher their deep structures. Following structural analysis, six images of the child are discerned, namely - the child as valuable, the child as a sacrificial object, the child as a saviour, the child as foolish/stubborn, the child as insolent and the child as violent. It is observed that the Igbo aetiological tales are multifunctional in that, aside from helping to assign reasons behind many situations, they also help to explain the rationale behind some Igbo customs and practices. Even more, they reveal the Igbo ideology about the child. It is hoped that the study will, among other things, provide an in-depth understanding of Igbo philosophy.